Etika dan Spiritualitas Islam Jawa dalam Pemikiran Moral Sosrokartono - Muniri, Muniri (Postgraduate Studies UIN Sunan Ampel Surabaya, 2023)
This study originates from the academic need to explore the dimensions of Javanese Islamic ethics and spirituality within the moral thought of Sosrokartono, a Nusantara intellectual who bridged Western scholarship and Eastern wisdom. Sosrokartono was renowned not only for his mastery of multiple languages but also for his worldview that reflected a synthesis of universal moral values and Islamic spirituality rooted in Javanese culture. The urgency of this research lies in revealing the relevance of Sosrokartono’s thought to the formation of ethical and spiritual character in modern Indonesian society. The study employs a historical research method with a qualitative interpretative approach, encompassing the stages of heuristics, verification, interpretation, and historiography, as developed by Nugroho Notosusanto. The findings indicate that Sosrokartono’s moral philosophy embodies Javanese Islamic values such as ngelmu kasampurnan (the pursuit of perfection), laku prihatin (ascetic discipline), and tepa selira (empathy and tolerance), integrated with universal human ethics. The novelty of this research lies in its integrative interpretation of Sosrokartono as a representation of Javanese Islamic ethical spirituality that remains contextually relevant to contemporary moral challenges.